2013
DOI: 10.1177/2050640613480145
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transhepatic and extrahepatic routes for EUS‐guided rendezvous procedure for distal CBD obstruction

Abstract: Background: EUS-guided rendezvous procedure (EUS-RV) can be done by the transhepatic (TH) or the extrahepatic (EH) route. There is no data on the preferred access route when both routes are available. Study aim: To compare the success, complications, and duration of hospitalization for patients undergoing EUS-RV by the TH or the EH route. Patients and methods: Patients with distal common bile duct (CBD) obstruction, who failed selective cannulation, underwent EUS-RV by the TH route through the stomach or the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 10 publications
0
62
0
1
Order By: Relevance
“…Some centers therefore prefer the IHBD approach [25,31]. Dhir et al, however, showed in a retrospective cohort of 35 patients that IHBD approach required significantly longer procedure time and higher incidence of post-procedural pain [32]. Hospital stay was also longer.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Some centers therefore prefer the IHBD approach [25,31]. Dhir et al, however, showed in a retrospective cohort of 35 patients that IHBD approach required significantly longer procedure time and higher incidence of post-procedural pain [32]. Hospital stay was also longer.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Logistic regression analysis also showed transhepatic access to be the only independent risk factor for complications. In another retrospective cohort, extrahepatic vs intrahepatic access PS plastic stent route in EUS-RV was compared [32]. Both access routes have similar technical and clinical success rate, but extrahepatic access was associated with significantly shorter procedure and hospitalization time and with less complications.…”
Section: Eus-guided Extrahepatic Biliary Drainage Vs Eus-guided Intramentioning
confidence: 98%
“…13 Since 2008, multiple studies on EUS-BD by experienced endoscopists and involving more than 15 patients per study have been reported, with technical and functional success rates between 73% and 98% and 75% and 100%, respectively, and adverse event rates between 3% and 23%. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] EUS-BD is becoming an established technique for biliary access after failed ERCP in specialized centers and, like all new interventions, requires ongoing evaluation to establish its role in clinical practice. The aim of this study was to establish how often EUS-BD is really needed in tertiarycare level therapeutic endoscopy unit and to assess whether the degree of excitement, hype, and investment in EUS-BD is warranted, given the predicted need for biliary drainage after failed ERCP.…”
mentioning
confidence: 99%
“…Data on long-term stent patency are scant, but do not seem to differ significantly to that of ERCP stenting [7] . With regards to the access route, transgastric and transduodenal endoscopic approaches have similar success rates and complications, of more than 90% and around 20% respectively [12][13][14][15][16] . As a matter of fact, the access route is often determined more by the endoscopist's expertise or preference than by evidence-based indications.…”
Section: Discussionmentioning
confidence: 99%